Mitigation of Impact of Climate Change through Watershed Management - Tripathi, K P; Sharda, V N (Journal of Agricultural Engineering, 2011)
Climate change during 21st century is projected to alter rainfall, and consequently the runoff and soil loss. The researchers worldwide are assessing the technical feasibility of the options to mitigate the impact of harmful gases (CO2, CH4 and others). The experiences gained by different institutions in India and worldwide have amply demonstrated the positive outcome of soil and water conservation measures implemented on watershed basis both under drought and abnormal rainfall conditions. Simple measures like strengthening of field bunds, contour bunding, trenching, vegetative barriers, agro-forestry, water harvesting and afforestation of denuded land along with other engineering and biological measures are found to be suitable options to mitigate the adverse impacts of climate change. These measures are, however, likely to be more expensive. Analysis showed that percent increase in the cross section of field bunds in medium soil is expected to be 33.3, 71.1 and 113.3% with an expected increase in one day maximum rainfall by 20, 40 and 60%, respectively, over the cross section corresponding to the one day maximum for the base period of 1961-1990. Similarly, the cross section of the field bunds in light textured soil is expected to be 30.9, 65.5 and 103.6% for the same increase in one day maximum rainfall. It is also projected that about 17% of additional earth work would be required in bunding (contour or graded) if one day maximum rainfall increases by 20 percent. Additional earthwork would increase to 80% with increase in rainfall by 100 percent. The earth work of trenching is projected to be directly proportional to the increase in daily rainfall. The analysis showed that the watershed management practices, though very effective mitigation options under adverse climatic conditions, are likely to be more expensive. To overcome the increasing cost of soil and water conservation measures, appropriate cost effective bio-engineering measures need to be evolved.